ANTECEDENTS OF REVISIT INTENTION OF GENERATION Z AT COFFEE SHOPS IN INDONESIA - Feriyawati, Windy; Willy; Yaputra, Hermanto; Setia, Bayu (Jurnal Riset Bisnis dan Manajemen, 2026)
This study analyzes the effects of Brand Attachment, Brand Characteristics, Service Quality, Servicescape, and Food and Beverage Quality on Revisit Intention, mediated by Customer Brand Attitude and Customer Satisfaction. The sample consists of 500 Generation Z consumers from five coffee shop brands in Jakarta. Data were analyzed using Structural Equation Modeling (SEM) with AMOS. The findings show that Brand Attachment and Brand Characteristics significantly influence Customer Brand Attitude, while Service Quality and Food and Beverage Quality positively affect Customer Satisfaction. Both mediating variables significantly influence Revisit Intention and mediate the relationships between antecedent variables and Revisit Intention. In contrast, Servicescape does not significantly affect Customer Satisfaction among Generation Z consumers. This study contributes to service marketing literature by integrating branding and quality perspectives. However, the cross-sectional design and geographic focus limit generalizability.